Kebermanfaatan Tahanan Pendamping (Tamping) dalam Operasional Sistem Lembaga Pemasyarakatan - Ciek Julyati Hisyam; Dina Lestari; Hilyatussholehah Hilyatussholehah; Ona Rangratu; Ridho Syafiq; Silviana Dwi Anggraeni (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Correctional institutions have very few employees compared to the prisoners who become prisoners. Therefore, the operation of the penitentiary system involves personnel from tamping in order to carry out operations optimally. This study aims to explain the existence of tamping as an auxiliary force for the operation of correctional institutions. The research method was conducted with a descriptive method through a qualitative approach and using data collection techniques with in-depth interviews with 3 key informants and 3 informants. This research is located in an urban area of Bandung, precisely in prisons X and Y. The results state that the prison organization can operate optimally because it is assisted by assistants who are more numerous than prison officers.